PENGUJIAN ANOMALI PASAR DI PASAR MODAL INDONESIA: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Elsi Agustin; Faisal Faisal (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
Abstract: This study aims to determine market anomalies in the Indonesian capital market which focuses on the LQ 45 Index for the period January 2011 – December 2021. The anomalies discussed are seasonal anomalies or Seasonal Anomaly which include the Day of the Week Effect (Monday Effect and Weekend Effect) and Month of The Year Effect (January Effect). The data used is secondary data obtained from the IDX and Yahoo Finance sites. The data analysis method used is regression analysis using the OLS and GARCH models processed with Eviews. The results of the study found that there were market anomalies in the LQ 45 Index for the period January 2011 – December 2021, which are the Day of the Week Effect (Monday Effect) and the Month of The Year Effect (December Effect). The results of the study also found that there was no Weekend Effect on the LQ 45 Index for the period January 2011 – December 2021. Keywords: Efficient Market Hyphothesis, Market Anomaly, Seasonal Anomaly, Monday Effect, Weekend Effect, January Effect Abstrak: Penelitian ini bertujuan untuk mengetahui anomali pasar di pasar modal Indonesia yang berfokus di Indeks LQ 45 Periode Januari 2011 – Desember 2021. Anomali yang dibahas adalah anomali musiman atau Seasonal Anomaly yang meliputi Day of The Week Effect (Monday Effect dan Weekend Effect) dan Month of The Year Effect (January Effect). Data yang digunakan merupakan data sekunder yang diperoleh dari situs IDX dan Yahoo Finance. Metode analisis data yang digunakan adalah analisis regresi menggunakan model OLS dan GARCH yang diolah dengan Eviews. Hasil penelitian menemukan bahwa terdapat anomali pasar di Indeks LQ 45 periode Januari 2011 – Desember 2021, yang mana anomali tersebut adalah Day of The Week Effect (Monday Effect) dan Month of The Year Effect (Efek bulan Desember). Hasil penelitian juga menemukan bahwa tidak terjadi Weekend Effect di Indeks LQ 45 periode Januari 2011 – Desember 2021. Kata Kunci: Efficient Market Hyphothesis, Market Anomaly, Seasonal Anomaly, Monday Effect, Weekend Effect, January Effect